Lettuce production in hydroponic and fish-farming aquaponic under different channel slopes and nutrient solutions in the NFT system - Vinícius V. O. Mendonça; César A. da Silva; Claudia R. O. S. G. Mendonça; Cícero J. da Silva; Claudinei M. Guimarães (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The slope of cultivation channels and types of nutrient solutions in hydroponics and aquaponics influence nutrient absorption and plant production. This research aimed to evaluate lettuce production under different channel slopes and nutrient solutions in hydroponic and aquaponic systems using the nutrient film technique (NFT). A randomized block design was used, with three replicates, in a 3 × 5 split-plot scheme, with three nutrient solutions (conventional hydroponic solution and two wastewaters from the tilapia fish diets, with 15 and 18% of crude protein) and five slopes (2, 4, 6, 8 and 10%) of cultivation channels (PVC tubes). The following variables were evaluated: fresh and dry mass of shoot and roots and the chemical elements of the solutions. In the tilapia feed, the nutrient solution with 18% of protein (wastewater) provides greater production and accumulation of nutrients (N and P) in the lettuce shoot. The slope of 8% on cultivation channels provides greater production of iceberg lettuce, cultivar Lucy Brown. The different slopes and nutrient solutions studied did not influence the potassium (K) accumulation in the lettuce shoot.